Efficiency of high-order accurate difference schemes for the korteweg-de vries equation - Poochinapan,K. (Hindawi Publishing Corporation, 2015)
© 2014 Kanyuta Poochinapan et al. Two numerical models to obtain the solution of the KdV equation are proposed. Numerical tools, compact fourth-order and standard fourth-order finite difference techniques, are applied to the KdV equation. The fundamental conservative properties of the equation are preserved by the finite difference methods. Linear stability analysis of two methods is presented by the Von Neumann analysis. The new methods give second- and fourth-order accuracy in time and space, respectively. The numerical experiments show that the proposed methods improve the accuracy of the solution significantly.